Transverse changes after surgically assisted rapid palatal expansion - Gurgel, Júlio de Araújo [UNESP]; Tiago, C. M.; Normando, D. (Churchill Livingstone, 2014)
The aim of this retrospective study was to investigate the amount of skeletal and dental expansion in patients submitted to surgically assisted rapid palatal expansion (SARPE). The sample consisted of 21 patients (14 female and seven male) with a mean age of 25.4 years (range 17.4-41.8 years). Postero-anterior (PA) cephalograms were taken pre-expansion (T1), immediately after expansion (T2), and at post-expansion retention of 120 days (T3). SARPE promoted significant transverse skeletal changes, which were maintained from T2 to T3. Dentoalveolar expansion and dental tipping were also observed in the region of the first molars and first premolars; however the net effect at the first molars was significantly less than that at the first premolars. No statistically significant effect on the width of the nasal cavity was observed. The findings indicate that peculiarities inherent to dental effects may influence the clinical options for SARPE. Skeletal expansions with SARPE were significant and stable. Dental changes were different between molars and premolars. The transverse changes after SARPE should be observed for future procedures related to the retention and the completion of orthodontic treatment.
Keywords: surgically assisted rapid palatal expansion; rapid maxillary expansion; dentoalveolar changes